Work-family conflict and job crafting in a diary study: the moderator role of work-family climate - Tavares, S. M.; Sanz-Vergel, A. (18th European Congress of Work and Organizational Psychology, 2017)
Purpose This study aimed to investigate whether feeling that work collides with one’s family life (work-family conflict, WFC) influences the way people proactively initiate changes in their tasks and in the social boundaries at their work (job crafting). Work climate for family sacrifice was tested as a boundary condition for that effect. Design/Methodology We conducted a diary study with 66 employees over 8 working days. Results Results showed that depending on the perceptions people had about the school’s climate for family sacrifice,they used different daily job crafting strategies to cope with the WFC they felt on a diary basis. When teachers considered that their school would expect them to sacrifice their family in favor of their job, they actively looked for social resources as a way of coping with the daily WFC experienced. However, when the climate for family sacrifice was perceived to be low, teachers delt with daily WFC lowering their enactement of developmental job crafting behaviours. Limitations Although we assessed our variables at different points in time during the working days, our correlational data structure does not allow to draw causal conclusions. Research/Practical Implications Our findings suggest that if managers want their employees to craft their job through searching for more developmental challenges, they should create conditions to develop a climate where the employees would not be expected to sacrifice their families and also create the conditions to lower their experience of WFC. Originality/Value This paper brings together the literature on work-family interface and job crafting, what is a new approach.